Automated Guide Vehicles Dynamic Scheduling Based on Annealing Genetic Algorithm - Zou Gan; Li Tao; Qin Ying (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Dispatching automated guided vehicles (AGVs) is the common approach for AGVs scheduling in practice, the information about load arrivals in advance was not used to optimize the performance of the automated guided vehicles system (AGVsS). According to the characteristics of the AGVsS, the mathematical model of AGVs scheduling was established. A heuristic algorithm called Annealing Genetic Algorithm (AGA) was presented to deal with the AGVs scheduling problem,and applied the algorithm dynamically by using it repeatedly under a combined rolling optimization strategy. the performance of the proposed approach for AGVs scheduling was compared with the dispatching rules by simulation. Results showed that the approach performs significantly better than the dispatching rules and proved that it is really effective for AGVsS. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2481